AMUSEMENT PARK ENVIRONMENT EFFECT ON VISITORS MOOD - Riztya Putri Ramadhany; Niken Laksitarini (Ide dan Dialog Desain Indonesia (Idealog), 2021)
Psychologically, entertainment becomes a secondary human need. An amusement park is one of the entertainment destinations in various countries. An amusement park is designed to have a charm that can attract visitors' attention and provide pleasure or emotional response to visitors. This research is an analytical study of the amusement park environment and its effect on visitors’ moods based on spatial psychology. This study aimed to find out how an amusement park can affect the mood of its visitors from the variables, namely the design approach, amusement rides, and public facilities. The object of research used to analyze these variables is the Saloka Park located in Semarang, Central Java. The research method used was qualitative research with literature analysis methods as well as direct observation and questionnaires to visitors in Saloka Park. In addition, indirect observations were also carried out on the comparison object, Tokyo Disneyland, which is one of the largest theme parks in the world. The results of this study indicate that the design approach, amusement rides, and public facilities in the amusement park environment have certain psychological impacts that automatically affect human feelings in response to the environment. Of the three variables, amusement rides are the variables that contribute the most to mood changes of amusement park visitors. Keywords: Amusement park, mood, space psychology